(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The objective of this study is to analyse the within group improvement in two experimentalgroups and one control group on the performance of the field hockey sixteen yard hitting skill test due tokinaesthetic perception drills.In this study Descriptive statistics was used for to compare within groupdifference was analysed using paired‟„t‟ test and the difference between experimental and control groupwas using the information studying tools spss- 21 software turned into used.The purpose of this studyis to find out to comparative effect of visual and auditory perception sixteen yard hitting test drills on thehockey performance. The objective of this study is to analyse the within group improvement in twoexperimental groups and one control group on the performance of the field hockey sixteen yard hittingtest due to kinaesthetic perception drills. The study was select to 14 to 18 years of hockey players ofIndore district participating at different levels of achievement and who voluntary opt hockey for theirsports period. The study was further defined to the basic skills of sixteen yard hitting test, The totalnumber ,of subjects forty five (N = 45) subjects from three groups two experimental groups and onecontrol groups were selected for the each group equal subjects fifteen (15) for this study age rangedbetween 14-18 years players of Hockey comprising from Indore district, who voluntary opt hockey fortheir sports period. In this study Descriptive statistics was used, the within group difference wasanalysed using paired‟ test and the difference between experimental and control group was analysed thedata analysing tools SPSS- 21 software was used. The level of significance was set at 0.05 level. Therewas significance Mean effects of two experimental and one control groups Sixteen yard hitting test ofkinaesthetic perception drills of hockey performance.